2015
DOI: 10.1039/c5mt00163c
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic phosphino copper(i) complexes with in vitro and in vivo dual cytotoxic and anti-angiogenic activity

Abstract: Homoleptic, tetrahedral Cu(i) complexes of the type [Cu(P)4]BF4 (1-3), where P are the phosphine ligands, 1,3,5-triaza-7-phosphaadamantane (PTA), 3,7-diacetyl-1,3,7-triaza-5-phosphabicyclo[3.3.1]nonane (DAPTA) and 2-thia-1,3,5-triaza-phosphoaadamantane-2,2-dioxide (PTA-SO2), have been prepared. Novel complexes [Cu(DAPTA)4]BF42 and [Cu(PTA-SO2)4]BF43 have been fully characterized by means of spectroscopic methods, corroborated by XAS-EXAFS analysis of 2. In vitro cell culture experiments revealed a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Complexes [Cu(PTA) 2 ] + , [Cu(PTA) 3 ] + and [Ag(PTA) 2 ] + are predicted to be the species involved in the cytotoxic mechanism of these compounds. [36] Furthermore, the complex [Cu(THP) 4 ]PF 6 displays efficacy in the treatment of Lewis pulmonary tumour in mice in both early and advanced stage treatment schedule. [35] Complex 39 is neurotoxic, and produces the inhibition of proteasome activity in DRG neurons even at lower concentrations than the IC 50 , while copper complex 37 does not induce neurotoxicity.…”
Section: Complexes With Pta and Derivatives Different To Dmoptamentioning
confidence: 99%
“…Complexes [Cu(PTA) 2 ] + , [Cu(PTA) 3 ] + and [Ag(PTA) 2 ] + are predicted to be the species involved in the cytotoxic mechanism of these compounds. [36] Furthermore, the complex [Cu(THP) 4 ]PF 6 displays efficacy in the treatment of Lewis pulmonary tumour in mice in both early and advanced stage treatment schedule. [35] Complex 39 is neurotoxic, and produces the inhibition of proteasome activity in DRG neurons even at lower concentrations than the IC 50 , while copper complex 37 does not induce neurotoxicity.…”
Section: Complexes With Pta and Derivatives Different To Dmoptamentioning
confidence: 99%
“…In this regard, copper has attracted significant interest, since it plays key roles in biochemical processes such as nitrite reductase22, amine oxidases23, superoxide dismutase24, catechol oxidase25 and tyrosinase26. Copper(II) complexes have been intensily studied1027 whereas the potential of Cu(I) complexes has been scarcely tested as antimicrobial28, antiviral29, antifungal30 and anticancer drugs1731323334. Mostly, coordination compounds having S-/N-donor and/or phosphine ligands are highly suitable candidates for clinical investigation, given their proven cytotoxicity on cancer cells and high stability in aqueous solution35.…”
mentioning
confidence: 99%
“…Cu in the form of salt (CuSO 4 ) or nanoparticles, when introduced into chicken embryos did not interfere with embryonic growth or development, but has been shown to increase angiogenesis via increasing the mRNA of activators like VEGF and FGF (Mroczek-Sosnowska et al, 2015). Recently, in few reports, contradictory to previous findings, Cu has been found to be anti-angiogenic too (Chang et al, 2015;Gandin et al, 2015 …”
Section: Introductionmentioning
confidence: 54%
“…Chang et al (2015) revealed that CuO nanoparticles down-regulated the expression of vascular endothelial growth factor (VEGF) and VEGF receptors in endothelial cells. Homoleptic phosphino copper (I) complexes also repressed angiogenesis by inhibiting the fundamental steps of blood vessel formation like endothelial cell adhesion, migration, alignment, protease secretion and tubule formation (Chang et al, 2015;Gandin et al, 2015). The reason behind the contradictory behaviour can be explained on the basis of nature of material used for study, like solubility, ionic strength, dissociation constant and pH change in microenvironment surrounding the affected area.…”
Section: Discussionmentioning
confidence: 99%